Multi-shelled hollow architecture enabling synergistic multi-transportation pathway for Li+ in composite quasi-solid electrolyte - Lili Lan; Xinhong Qi; Xiongbin Yang; Shichen Zhang; Yihang Li; Lu Gao; Xiaobin Jiang; Xiangcun Li; Gaohong He (Chemical Engineering Journal, 2026)

Diversified cropping combined with nutrient optimization regulates microbial resource limitations, thereby influencing ecoenzymatic carbon and nitrogen use efficiencies - Wei Zhang; Wanting Li; Zhuolin Li; Xinlei Li; Ruqi Duan; Dexiang Luo; Guohui Xiong; Mingmin Li; Jun Tao; Shichen Li; Yingfen Yang; Zhengxiong Zhao (Agriculture, Ecosystems & Environment, 2026)

Lagged crop responses to drought across China: contrasting multivariate environmental pathways in rainfed and irrigated systems - Rui Yang; Litao Zhou; Hao Yuan; Xinyi Han; Jianhang Zhang; Jiayu Bao; Pengzhou Chen; Shichen Gao; Jianjun Wu (Journal of Environmental Management, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Critical role of mid-elevation in microbial regulation of soil carbon dynamics on the southern foothills of the Qinling Mountains - Ermao Ding; Fanglin Shen; Tengyue Du; Xian Ren; Shichen Wang; Lirong Zhao; Liping Hu; Jie Yang; Yue Hu; Weibo Shen (CATENA, 2025)

Early diagenesis of coral rubble on the high-energy platform of Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Shichen Tao; Xiyang Zhang; Hongqiang Yan; Zhiwei Hou; Ji Yang; Wenlong Jing; Pin Yan (Marine Geology, 2025)

Super paleo-typhoons striking southern Hainan Island in the northern South China Sea during the mid-late Holocene: Coral boulder evidence from a fringing reef - Shengnan Zhou; Qi Shi; Shichen Tao; Xiyang Zhang; Hongqiang Yan; Huiling Zhang; Zhiwei Hou; Wenlong Jing; Ji Yang (Global and Planetary Change, 2025)

Numerical investigation on a quaternary-driven rotary energy recovery device for desalination system: Performance evaluation and theoretical validation - Jie Zhou; Han Qi; Ziyu Wen; Qinghong Zhang; Naitao Yang; Shichen Mu (Desalination, 2025)

An Ensemble Classification Method Based on a Stacking Strategy for Ship Type Classification with AIS Data - Lei Deng; Shichen Yang; Limin Jia; Danyang Geng (Journal of Marine Science and Engineering, 2025)
Ship type (e.g., Cargo, Tanker and Fishing) classification is crucial for marine management, environmental protection, and maritime safety, as it enhances navigation safety and aids regulatory agencies in combating illegal activities. Traditional ship type classification methods with AIS data are often plagued by problems such as data imbalance, insufficient feature extraction, reliance on single-model approaches, or unscientific model combination methods, which reduce the accuracy of classification. In this paper, we propose an ensemble classification method based on a stacking strategy to overcome these challenges. We apply the SMOTE technique to balance the dataset by generating minority class samples. Then, a more comprehensive ship behavior model is developed by combining static and dynamic features. A stacking strategy is adopted for the classification, integrating multiple tree structure-based classifiers to improve classification performance. The experimental results show that the ensemble classification method based on the stacking strategy outperforms traditional classifiers such as CatBoost, Random Forest, Decision Tree, LightGBM, and the ensemble classification method, especially in terms of improving classification precision, recall, F1 score, ROC curve, and AUC. This method improves the accuracy of ship type recognition, and it is suitable to real-time online classification, which is helpful for applications in marine safety monitoring, law enforcement, and illegal fishing detection.

Metal organic frameworks intensify lithium ion conduction and SEI formation inlayed in solid electrolyte facing with lithium metal anode - Shichen Zhang; Yihang Li; Jinzhong Liu; Xiongbin Yang; Xinhong Qi; Xiangcun Li; Gaohong He (Chemical Engineering Journal, 2025)

Unraveling the role of pyrolysis temperature in biochar-mediated modulation of soil microbial communities and tobacco bacterial wilt disease - Shichen Li; Linyuan Yang; Tao Jiang; Waqar Ahmed; Fupeng Mei; Jinhao Zhang; Tao Zhang; Yingfen Yang; Xiaoci Peng; Qu Shan; Dexiang Luo; Zhengxiong Zhao (Applied Soil Ecology, 2025)

Visual study of hydrate particles agglomeration and rolling characteristic in gas-oil-water phase using a flow loop - Zheyuan Liu; Shichen Shen; Binlin Dou; Ni Liu; Liang Yang; Mingjun Yang; Yongchen Song (Fuel, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Genotype of pioneer plant Miscanthus is not a key factor in the structure of rhizosphere bacterial community in heavy metal polluted sites - Danni Liu; Ying-heng Fei; Yuxin Peng; Shichen Zhu; Jianan Lu; Yang Luo; Ziwu Chen; Yuanyuan Jiang; Shizhong Wang; Ye-Tao Tang; Rongliang Qiu; Yuanqing Chao (Journal of Hazardous Materials, 2024)

Study on the active regeneration characteristics of DPF in diesel-methanol dual-fuel engine under different exhaust oxygen concentrations - Shichen Yang; Mingding Wan; Zhengjiang Wang; Lizhong Shen; Fenlian Huang; Yuting Ma; Yuhan Xiao (Fuel, 2024)

Improved texture properties and toughening mechanisms of surimi gels by double network strategies - Shichen Zhu; Yingying Wang; Yicheng Ding; Xingwei Xiang; Qing Yang; Zhengpeng Wei; Hua Song; Shulai Liu; Xuxia Zhou (Food Hydrocolloids, 2024)

Investigation on the operating capacity expansion through parallel schemes of reciprocating-switcher energy recovery device for desalination: Simulation, verification and parameterization - Jie Zhou; Dong Liu; Qinghong Zhang; Chao Bian; Xiuxia Meng; Naitao Yang; Shichen Mu (Desalination, 2024)

Different Morphologies and Functional Nitrogen Accumulation Results in the Different Nitrogen Use Efficiency of Tobacco Plants - Shichen Li; Waqar Ahmed; Tao Zhang; Tao Jiang; Fupeng Mei; Qu Shan; Linyuan Yang; Cuilian Guo; Zhengxiong Zhao (Journal of Plant Growth Regulation, 2023)

A comparative study on the taste quality of Mytilus coruscus under different shucking treatments - Shichen Zhu; Lin Zhu; Zhigang Ke; Hui Chen; Yadan Zheng; Peng Yang; Xingwei Xiang; Xiaomin Zhou; Youding Jin; Shanggui Deng; Xuxia Zhou; Yuting Ding; et al. (Food Chemistry, 2023)

Tumor-derived microparticles-based nanomaterial as platform for delivery of tumor antigens to enhance immunogenicity - Qi Tan; Zimo Yang; Shichen Bu; Jiangbin Chen; Wenjuan Chen; Wei Geng; Qi Huang; Limin Duan; Mengfei Guo; Yali Wu; Jingjing Deng; E Zhou; et al. (Chemical Engineering Journal, 2023)

Acute Transcriptomic and Epigenetic Alterations at T12 After Rat T10 Spinal Cord Contusive Injury - Junkai Xie; Seth Herr; Donghan Ma; Shichen Wu; Han Zhao; Siyuan Sun; Zhixiong Ma; Matthew Yan-lok Chan; Katherine Li; Yang Yang; Fang Huang; Riyi Shi; et al. (Molecular Neurobiology, 2023)

Performance characteristics and bacterial community analysis of a novel two-step-feed three-stage A/O-MBBR system for nitrogen removal in municipal wastewater - Xiaolin Zhou; Zijian Jiang; Jinzhao Gu; Xuejun Bi; Jingmiao Liu; Xuyi Wang; Tang Yang; Xueqing Shi; Lihua Cheng; Shujuan Huang; Xiaodong Wang; Harsha Ratnaweera; et al. (Journal of Water Process Engineering, 2023)

Meridional response of Western North Pacific paleocyclone activity to tropical atmospheric circulation variability over the past millennium - Fei Tan; Yunfeng Zhang; Li Cao; Huilong Xu; Qi Shi; Xiyang Zhang; Shichen Tao; Jianxin Zhao; Hongqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Identification of candidate genes for panicle length in Oryza sativa L. ssp. japonica via genome-wide association study and linkage mapping - Hongliang Zheng; Shichen Sun; Liangming Bai; Shukun Jiang; Guohua Ding; Tongtong Wang; Hongwei Zhao; Jingguo Wang; Hualong Liu; Luomiao Yang; Yan Jia; Xin Wei; et al. (Euphytica, 2022)

Comparative transcriptome analysis of salt-sensitive and salt-tolerant maize reveals potential mechanisms to enhance salt resistance - Mingquan Wang; Yufeng Wang; Yifei Zhang; Chunxia Li; Shichen Gong; Shuqin Yan; Guoliang Li; Guanghui Hu; Honglei Ren; Jianfei Yang; Tao Yu; Kejun Yang (Genes & Genomics, 2019)

Tissue-derived scaffolds and cells for articular cartilage tissue engineering: characteristics, applications and progress - Xuejian Liu; Haoye Meng; Quanyi Guo; Baichuan Sun; Kaihong Zhang; Wen Yu; Shichen Liu; Yu Wang; Xiaoguang Jing; Zengzeng Zhang; Jiang Peng; Jianhua Yang (Cell and Tissue Research, 2018)

Mapping novel aphid resistance QTL from wild soybean, Glycine soja 85-32 - Shichen Zhang; Zhongnan Zhang; Carmille Bales; Cuihua Gu; Chris DiFonzo; Ming Li; Qijian Song; Perry Cregan; Zhenyu Yang; Dechun Wang (Theoretical and Applied Genetics, 2017)

Development and validation of KASP markers for the greenbug resistance gene Gb7 and the Hessian fly resistance gene H32 in wheat - Chor-Tee Tan; Hangjin Yu; Yan Yang; Xiangyang Xu; Mingshun Chen; Jackie C. Rudd; Qingwu Xue; Amir M. H. Ibrahim; Lisa Garza; Shichen Wang; Mark E. Sorrells; Shuyu Liu (Theoretical and Applied Genetics, 2017)

A fractionation procedure for identifying novel proteins induced by chill stress in Arabidopsis thaliana - Liwen Sun; Shichen Wang; Jinghui Xi; Shuo Yang; Xiangguo Liu; Xin Chai; Hongbao Xin; Baiyi An; Dongyun Hao (Biotechnology Letters, 2009)

An in silico strategy identified the target gene candidates regulated by dehydration responsive element binding proteins (DREBs) in Arabidopsis genome - Shichen Wang; Shuo Yang; Yuejia Yin; Xiaosen Guo; Shan Wang; Dongyun Hao (Plant Molecular Biology, 2009)